Studi Literatur: Efektivitas Model Project Based Learning (PjBL) pada Pembelajaran di Sekolah Dasar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of the Project Based Learning (PjBL) model on student learning outcomes and skills at the elementary school level. The method used is a Systematic Literature Review (SLR) by reviewing and synthesizing 10 reputable journal articles published in the last three years from 2024-2025. The results of the study indicate that the implementation of PjBL can significantly improve students' conceptual understanding, independence, and problem-solving skills due to its relevance to real-life everyday experiences. Although proven effective, the success of this model is highly dependent on the role of the teacher as a facilitator and the readiness of supporting devices. Thus, PjBL is a very potential alternative learning strategy in elementary schools, as long as it is carefully planned according to the stage of students' cognitive development.